د ا رسة بعض المعايير الكيموحيوية في مصل دم المصابين بالفشل الكموي المزمن في محافظة كربلاء - الع ا رق - دلال عبد الحسين كاظم العيساوي (University of Thi-Qar Journal of Science, 2019)
This study was concluded in laboratories of the Hussien teaching hospital/department of industrialkidney in Karbala governorate during the period between 1/10/2011 to 1/4/2012 to fine the relationshipbetween some biochemical parameters and chronic kidney failure patients men.The study was carried out on(36) men that undergo from failure of the kidney chronic during their admission the hospatital then theresults that obtained compared with the control group that included (36) healthy male. The results revealedthat a significant increase (p<0.05) in urea, total keratinine and uric acid concentration in blood serumcompared with the control group, and a significant increase (p<0.05) in the potassium and sodium ionconcentration compared with the control group, but the results showed a significant decrease (p<0.05) in thecalcium ion concentration as compared with the control group.